Mysticism, Enchantment and Charisma Reincarnated: Nineteenth-Century Islamic Talismans, Vernacularization and Heritage Values in Contemporary Asante - Engmann, Rachel Ama Asaa (Material religion, 2019)
Condensed, concealed, inconspicuous material embodiments of mysticism, enchantment, and charisma, nineteenth-century Islamic talismans traveled the trans-Saharan caravan trade routes, circulating widely among the non-Muslim Asante, reflecting a tradition illustrative of the movement of people, objects, texts, ideas, and imaginations. Produced by migrant Muslim merchant-clerics and consumed by non-Muslim Asantes, they demonstrate the ways in which Islamic and non-Islamic traditions are inextricably intertwined. Deemed exceedingly efficacious, nineteenth-century Islamic talismans were conscripted for the Asante imperial project, chiefly, imperial expansion by combatting opposing social and political forces, namely, local insurgencies and British colonialism. Today, nineteenth-century Islamic talismans remain highly popular, continuing to circulate in local, regional, and national arenas as part of a contemporary living social tradition. Employing archaeological ethnography, this article examines how Muslims and non-Muslims mobilize nineteenth-century Islamic talismans in the present, critiquing Western Eurocentric heritage values that are oblivious to, and disregard Islam in Asante as a lived social and material praxis.